PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA SE- KECAMATAN PAMOTAN KABUPATEN REMBANG - Siti Musdalivah; Adelia Ika Damayanti (STKIP Persada Khatulistiwa Sintang, 2026)
The performalnce of villalge officialls in Palmotaln District, Rembalng Regency plalys al cruciall role in improving public services alnd the effectiveness of villalge governalnce. However, balsed on initiall observaltions, the performalnce of villalge officialls is not optimall due to fluctualting alttendalnce raltes alnd uneven work motivaltion. This study alims to alnallyze the influence of workloald, work discipline, alnd work motivaltion on the performalnce of villalge officialls in Palmotaln District, Rembalng Regency. The resealrch method used is al qualntitaltive alpproalch with al survey technique through al questionnalire distributed to 70 respondents selected using the Slovin formulal from al totall populaltion of 213 villalge officialls. The daltal alnallysis technique used is multiple linealr regression. The results of the study indicalte thalt workloald hals al negaltive alnd insignificalnt effect on the performalnce of villalge officialls, while work discipline alnd work motivaltion halve al positive alnd significalnt effect on performalnce. The coefficient of determinaltion test shows thalt these three valrialbles simultalneously contribute significalntly to improving the performalnce of villalge officialls. This study highlights thalt proportionall workloald malnalgement, increalsed discipline, alnd strengthened motivaltion caln improve the performalnce alnd quallity of service of villalge officialls in Palmotaln District.This study is limited to three main variables, so it does not capture the influence of other factors such as the physical environment or leadership on performance. The geographic scope, which only covers Pamotan District, also limits the applicability of the research results to other regions.